Sociodemographic disparities in gastric cancer and the gastric precancerous cascade: A population-based study - Dianqin Sun; Lin Lei; Changfa Xia; He Li; Maomao Cao; Siyi He; Zhiyi Zhang; Guizhou Guo; Guohui Song; Ji Peng; Wanqing Chen (Elsevier, 2022)
Summary: Background: Gastric carcinogenesis is a multistep process initiating with chronic gastritis and progressing through atrophy, intestinal metaplasia, and dysplasia to carcinoma. This study aims to comprehensively investigate sociodemographic disparities in each stage of gastric carcinogenesis and estimate to what extent the inequalities could be ascribed to risk factors of gastric cancer (GC). Methods: We used the baseline data from a community-based study in China's high-risk areas, totalling 27094 participants. Gastric mucosa status was ascertained by endoscopy and biopsies. An overall socioeconomic status (SES) variable was generated by latent class analysis. We calculated relative risks (RRs) and 95% confidence intervals (CIs) using modified Poisson regression to assess associations of sociodemographic factors with each cascade stage. We estimated the percentage of the excess risk for neoplastic lesions among vulnerable populations that can be explained by established risk factors. Results: Age and sex showed associations with all gastric lesions, whose RRs increased with lesion progressing. Compared with individuals without schooling, the RRs of neoplastic lesions for people with primary, secondary, and post-secondary education were 0·86 (95% CI 0·76-0·97), 1·00 (95% CI 0·88-1·13), and 0·70 (95% CI 0·47-1·03), respectively. Participants with medium SES had a lower risk of neoplastic lesions than people in the low SES group (RR 0·83, 95% CI 0·74-0·93). GC risk factors could explain 33·6% of the excess risk of neoplastic lesions among men and a small proportion of the disparities among SES groups. Interpretation: Age and sex were essential sociodemographic factors for GC and precursor diseases. Individuals with low educational levels or SES were more likely to have neoplastic lesions. About one-third of the sex difference and a slight fraction of the socioeconomic inequalities could be attributed to included risk factors. Funding: Sanming Project of Medicine in Shenzhen, National Natural Science Foundation, and Special Project of Bejing-Tianjin-Hebei Basic Research Cooperation.